Avaliação da remoção de sulfametoxazol, diclofenaco e 17β-estradiol em água por meio de processo oxidativo com cloro - Souza, Brígida Prieto de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study aimed to evaluate removing of sulphamethoxazole, diclofenac and 17β-estradiol on distilled and natural waters by oxidation with chlorine. The results indicated that the initial concentrations of microcontaminants as the inicial time, had a significant differences in both waters of study. For the tests in distilled water, high values of removing were found. The natural water was treated by clarification followed by post-chlorination and the results revealed that the best removal efficiency occurred for diclofenac then 17β-estradiol and sulphamethoxazole. In accordance with the Decree 2914/11, which establishes values of pH, temperature and contact time basis on the residual chlorine, the corresponding time would be up to 10 minutes for post-chlorination, so the best values were on the order of 61% for the DCF, 36% to E2 and 33% for SMX in distilled water, in addition, for natural waters, these values were 34% for the DCF to 24% to E2 and 11% for SMX. The doses of chlorine were compared and in distilled water only the DCF had a significant differences in the removal efficiency with the increase of the applied dose (3.0 mg l -1 ), but in the SMX and E2 no significant differences were observed. It was observed the formation of the sub products of chlorination described by other researchers with these microcontaminants in natural water for SMX and E2 in concentrations from 20 to 90 μg.L-1. However was not found the formation of sub products to DCF, which presented a major removal values found in this study. For the oxidation kinetics of the studied drugs, the ideal contact time was observed in 30 minutes for most studies and all microcontaminants has better adjustment to the kinetic model of the pseudo-second order, with K2 values in the order of 0.0133 (DCF), 0.0168 (SMX) and 0.0326 (E2) in distilled water and 0.0092 (DCF), 0.0025 (SMX) and 0.0479 (E2) in natural water

O objetivo do presente trabalho foi avaliar a remoção de sulfametoxazol, diclofenaco e 17β- estradiol em águas destilada e natural através da oxidação com cloro. Os resultados indicaram que as concentrações iniciais dos microcontaminantes, bem como os tempos iniciais, apresentaram diferenças significativas na remoção dos fármacos em ambas às águas de estudo. Para os ensaios em água destilada, valores de remoção elevados foram encontrados. As águas naturais foram submetidas ao tratamento por clarificação seguido da pós-cloração e os resultados revelaram que a melhor eficiência de remoção deu-se para o diclofenaco, seguido do 17β-estradiol e do sulfametoxazol. De acordo com o estabelecido pela Portaria 2914/11, na qual estipula valores de pH, temperatura e tempos de contato em função do residual de cloro, o tempo correspondente seria até 10 minutos para a pós-cloração, assim, os melhores valores de remoção foram na ordem de 61% para o DCF, 36% para o E2 e 33% para o SMX em água destilada e para água natural esses valores foram de 34% para o DCF, 24% para o E2 e 11% para o SMX. As doses de cloro foram comparadas e para água destilada apenas o DCF apresentou diferenças significativas na eficiência de remoção com o aumento da dose aplicada (3,0 mg.L -1 ), porém para o SMX e E2 não foram observadas diferenças significativas. Observou-se formação de subprodutos já descritos por outros pesquisadores com esses microcontaminantes em água natural, para o SMX e E2 em concentrações de 20 a 90 μg.L -1, não apresentando formação de subprodutos para o DCF, o qual apresentou um dos maiores valores de remoção encontrados neste trabalho. Para cinética de oxidação dos fármacos o tempo de equilíbrio em 30 minutos foi observado para a maioria dos microcontaminantes estudados e todos se adequaram ao modelo cinético de pseudo-segunda ordem, com valores de K 2 na ordem de 0,0133(DCF), 0,0168(SMX) e 0,0326...
Keywords: Águas residuais - Purificação; Agua - Purificação; Fármacos; Desreguladores endócrinos; Oxidação; Cloro; Sewage -- Purification